Application of Restorative Justice to Solution of Traffic Accidents - Iman Faturrahman; Bambang Tri Bawono (Jurnal Daulat Hukum, 2021)
The purpose of this research is to find out and analyze the Application of Restorative Justice to the Resolution of Traffic Accidents. To know and analyze the ideal justice regulations in the application of Restorative Justice on Traffic Accident Settlement. In this study, the approach method used is the sociological juridical approach method. The result of this research is the application of Restorative Justice to the Resolution of Traffic Accidents has often been done by the police, especially traffic accidents and the most common is family group conferencing, because in this case this application is more active where the whole family both the victim and the perpetrator have met in a legal solution to the problem.